1971
DOI: 10.1021/ma60022a028
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Mechanism of Elastomeric Block Copolymers Having Spherical Domains of Hard Segments under Uniaxial Tensile Stress

Abstract: Elastomeric block copolymers are two-phase systems composed of spherical domains of a plastic component of colloidal dimensions dispersed in a matrix of rubber component. The deformation mechanism of such copolymers was investigated for A-B-type and A-B-A-type block copolymers of styrene and isoprene, as well as for mixtures of the A-B-type block copolymer with each corresponding homopolymer, by means of simultaneous measurements of the tensile stress-strain relation, small-angle light scattering, and small-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0

Year Published

1975
1975
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 1 publication
5
56
0
Order By: Relevance
“…Then the possible explanation for the deviation from the affine deformation exists in the sample, which is referred to as inner slippage, and void formation during the stretching may be responsible. Inoue et al reported a peculiar light scattering pattern (so-called butterfly pattern) for sphere-forming elastomeric block copolymer samples (comprising polystyrene and polyisoprene blocks) under stretched state at room temperature [17]. They ascribed the results to microvoid formation for which such a mechanism as that shown schematically in Figure 9 was also incorporated [17].…”
Section: As Clearly Seen Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Then the possible explanation for the deviation from the affine deformation exists in the sample, which is referred to as inner slippage, and void formation during the stretching may be responsible. Inoue et al reported a peculiar light scattering pattern (so-called butterfly pattern) for sphere-forming elastomeric block copolymer samples (comprising polystyrene and polyisoprene blocks) under stretched state at room temperature [17]. They ascribed the results to microvoid formation for which such a mechanism as that shown schematically in Figure 9 was also incorporated [17].…”
Section: As Clearly Seen Inmentioning
confidence: 99%
“…Inoue et al reported a peculiar light scattering pattern (so-called butterfly pattern) for sphere-forming elastomeric block copolymer samples (comprising polystyrene and polyisoprene blocks) under stretched state at room temperature [17]. They ascribed the results to microvoid formation for which such a mechanism as that shown schematically in Figure 9 was also incorporated [17]. This model can be explained as follows: In the initial stage before stretching, there is some extent of number density fluctuation of the hard spheres, which might be due to paracrystalline distortion, and the fluctuation is enhanced upon the stretching.…”
Section: As Clearly Seen Inmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17] The pioneering work of Hashimoto et al [8][9][10] investigated the deformation behavior of sphere forming SIS and cylinder-forming SBS copolymers. It was found that the deformation of sphere-forming copolymers deviates from affine behavior at quite small strain which is caused by the formation of cavities.…”
mentioning
confidence: 99%
“…Inoue, et al, (1969;Uchida, et al, 1972) assumed the absence of any mixed region between the domains and the matrix, with the polymer chains oriented normal to the domain interface at the junction point and were able to predict reasonably well (from statistical thermodynamics) the effect to Volume fraction of polystyrene and the nature of the solvent on the domain size and shape. Meier (1970) in similar calculations was also able to predict the most stable domain shape as a function of the block molecular weights in a diblock copolymer but without assuming anything regarding the orientation of the chains at the junction points.…”
Section: Ii) Theoretical Modelsmentioning
confidence: 99%
“…Contrary to the opinion and observations of certain early investigators (Beecher, et al, 1969, McIntyre andCampos-Lopez, 1970), the shape of the discrete polystyrene domains in SBS copolymers, containing about 27% by weight polystyrene, is not spherical. The domain shape appears to be nearly parallel, slightly curved, cylindrical rods of polystyrene in the polybutadiene matrix (Figure V-l) for solvent cast films (using a good solvent for both components) (Douy and Gallot, 1971, Hendus, et al, 1967, Inoue, et al, 1971, Krigbaum, et al, 1973, Lewis and Price, 1971, Turecek, 1972, Uchida, et al, 1972 for solvent cast films annealed at 100 0 C (Hoffman, et al, 1971) and for compression -51-1 molded samples (Lewis and Price, 1971) The spherical domains only appear in films of block copolymers containing 27% polystyrene cast from a poor solvent for the polystyrene block (e.g. cyclohexane) (Beecher, 1969, Inoue, et al, 1969 and in films of SBS copolymers containing less than 20% polystyrene .…”
Section: Surface Morphologymentioning
confidence: 99%